2017
DOI: 10.1093/cvr/cvx001
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of periostin inhibits post-infarction myocardial regeneration in neonatal mice mediated by the phosphatidylinositol 3 kinase/glycogen synthase kinase 3β/cyclin D1 signalling pathway

Abstract: AimsTo resolve the controversy as to whether periostin plays a role in myocardial regeneration after myocardial infarction (MI), we created a neonatal mouse model of MI to investigate the influence of periostin ablation on myocardial regeneration and clarify the underlying mechanisms.Methods and resultsNeonatal periostin-knockout mice and their wildtype littermates were subjected to MI or sham surgery. In the wildtype mice after MI, fibrosis was detectable at 3 days and fibrotic tissue was completely replaced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 58 publications
(112 reference statements)
6
61
0
Order By: Relevance
“…Furthermore, periostin also expressed myofibroblast in adult heart causes cardiac remodeling . In line with previous findings, neonatal mouse MI model also showed significantly increased mRNA expression of periostin at 1, 3, and 7 days after MI …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, periostin also expressed myofibroblast in adult heart causes cardiac remodeling . In line with previous findings, neonatal mouse MI model also showed significantly increased mRNA expression of periostin at 1, 3, and 7 days after MI …”
Section: Resultssupporting
confidence: 90%
“…There are several studies that have suggested that measurement of periostin may be of prognostic value. Such an association has been reported in CAD, HF, MI, and CVDs . In contrast, other study suggested that systemic periostin levels are largely determined by underlying pathogenesis of variety of cancer and allergic diseases, including asthma rather than cardiac function, and that prognostic significance does not remain after adjustment for underlying cardiac function .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our findings demonstrate increased angiogenesis, vasculogenesis, and widespread prosurvival changes in the myocardium, which indicate induction of a protective and restorative myocardial environment by AAMs. Interestingly, our results from proteomics showed significantly increased expression levels of the cardiomyocyte mitogen and matricellular protein POSTN (33,34) in both the subtransplant and remote septal zones, thus further strengthening the cellular and molecular mechanisms behind the observed functional improvement after AAM patch transplantation.…”
Section: Discussionsupporting
confidence: 59%
“…However, in the AAM and ECM patch groups, the fall in LVEF seemed considerably smaller in magnitude than that observed in the MI group. The acute declines in LVEF at one-week time-point postoperatively in AAM patch, ECM patch and MI groups were as follows: 18.03 (from 54.49±2.93% to 36.69±2.56%), 19.77 (from 52.15±3.10% to 32.38±2.96%) and 34.94 percent points (from 58.72±2.58% to 23.78±3.16%), respectively, with significant difference perceptible only between AAM patch and MI groups. However, since prevention of acute HF seemed evident in both patch groups, we hypothesize a considerable protective effect to occur by direct mechanical support, i.e.…”
Section: Myocardial Function Left Ventricular Ejection Fraction (Lvementioning
confidence: 98%